2006
DOI: 10.1186/1471-2458-6-72
|View full text |Cite
|
Sign up to set email alerts
|

The dimensions of responsiveness of a health system: a Taiwanese perspective

Abstract: Background: Responsiveness is an indicator used to measure how well a health system performs relative to non-health aspects. This study assessed whether seven dimensions proposed by the World Health Organization (WHO) to measure responsiveness (dignity, autonomy, confidentiality, prompt attention, social support, basic amenities, and choices of providers) are applicable in evaluating the health system of Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 12 publications
2
40
1
3
Order By: Relevance
“…The factor solutions from this study did not confirm the domain structure of 7 domains of previous studies [17]. This study underlines different clustering patterns of responsiveness for out-patients and in-patients in South Africa, in the Brazilian WHYS study [13] and in a study in Taiwan that found five factors (respect, access, confidentiality, basic amenities, and social support) [18]. For example, "autonomy" was in this and the Taiwanese study [18] not conceptualized as a unique domain.…”
Section: Discussioncontrasting
confidence: 81%
“…The factor solutions from this study did not confirm the domain structure of 7 domains of previous studies [17]. This study underlines different clustering patterns of responsiveness for out-patients and in-patients in South Africa, in the Brazilian WHYS study [13] and in a study in Taiwan that found five factors (respect, access, confidentiality, basic amenities, and social support) [18]. For example, "autonomy" was in this and the Taiwanese study [18] not conceptualized as a unique domain.…”
Section: Discussioncontrasting
confidence: 81%
“…Researchers have attempted to account for these differences in studies that have yielded different results [30, 31]. Second, responsiveness evaluations emphasize common and reasonable expectations; however, these are influenced by the characteristics of respondents, such as their age, education level, and income, thus introducing bias in expectations [19, 32]. Also, in our study, we investigated responsiveness of the general population rather than that of patients attending a specific hospital, public health service, or health center, which may have produced different results.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of the WHO survey on 191 countries demonstrated that responsiveness levels are generally higher in countries with higher individual health expenditures, several countries with health expenditures that are two or three times those of others obtained similar responsiveness [12]. An investigation in Taiwan likewise showed that various people concerned in the health system should be assessed during responsiveness comparisons, as this may present different weighted coefficients of responsiveness due to the diverse national cultures [13].…”
Section: Introductionmentioning
confidence: 99%